Molecular variability in the maize grey leaf spot pathogens in Brazil - Kátia R. Brunelli (Genetics and Molecular Biology, 2008)
Isolates of Cercospora species from leaves displaying symptoms of grey leaf spot were collected in maize-producing areas of south-central Brazil in 2001 and 2002. Restriction digests of the internal transcribed spacer region of rDNA detected the presence of the same two Cercospora species described on maize in the United States, namely C. zeae-maydis and the recently described species, C. zeina . Genetic variability among isolates was assessed by analysing 104 amplified fragment length polymorphism loci. Cluster analysis confirmed the genetic separation of isolates into two species with a mean similarity of 35%. Similarity levels within species were high, averaging 93% and 92% among isolates of C. zeae-maydis and C. zeina , respectively. The mean genetic similarity between C. zeae-maydis and C. zeina and two isolates of C. sorghi f. sp. maydis was 45% and 35%, respectively. Results of this study showed that populations of the grey leaf spot pathogens in Brazil are similar to those in the United States regarding species composition and that C. zeina is also present in Brazil.